2021
DOI: 10.21203/rs.3.rs-150639/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of The BHLH Transcription Factor Family and Its Response to Abiotic Stress in Sorghum [Sorghum Bicolor (L.) Moench]

Abstract: Background: Basic helix-loop-helix (bHLH) is a superfamily of transcription factors that is widely found in plants and animals, and is the second largest transcription factor family in eukaryotes after MYB. They have been shown to be important regulatory components in tissue development and many different biological processes. However, no systemic analysis of the bHLH transcription factor family has yet been reported in Sorghum bicolor. Results: We conducted the first genome-wide analysis of the bHLH transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 82 publications
(122 reference statements)
0
10
0
Order By: Relevance
“…The cDNA was produced with a 1 mg RNA sample using a PrimeScript RT Reagent Kit with gDNA Eraser (TaKaRa) and SYBR Premix Ex Taq II (TaKaRa) [85]. Total RNA was extracted using the RNA out Kit (TaKaRa) and treated with RNase-free DNase I to remove trace amounts of DNA.…”
Section: Total Rna Extraction Cdna Reverse Transcription and Qrt-pcr Analysismentioning
confidence: 99%
“…The cDNA was produced with a 1 mg RNA sample using a PrimeScript RT Reagent Kit with gDNA Eraser (TaKaRa) and SYBR Premix Ex Taq II (TaKaRa) [85]. Total RNA was extracted using the RNA out Kit (TaKaRa) and treated with RNase-free DNase I to remove trace amounts of DNA.…”
Section: Total Rna Extraction Cdna Reverse Transcription and Qrt-pcr Analysismentioning
confidence: 99%
“…The whole genomes of an increasing number of species have been sequenced, making it easy to identify gene families. In fact, many gene families in foxtail millet have been fully identified and analyzed, including bHLH [24], NAC [25], GRAS [26] and AP2/ ERF [27]. At present, the SPL gene families of several species have been extensively studied, including dicotyledons (Arabidopsis [18,28], tomato [22], Tartary buckwheat [23], grape [29], and cotton [30]), monocotyledons (rice [31,32], wheat [33], and barley [34]), and C4 crops (maize and Sorghum bicolor [35]).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the conservative protein motif pattern, AqbHLH family has diverse intron/exon organizations in the same subfamily and among different subfamilies. The phenomenon also was found in the bHLH gene family in Chinese white pear (Dong et al, 2021), sorghum (Fan et al, 2021) and tobacco (Bano and Patal, 2021). The result suggested that the AqbHLH gene family may play diverse roles in many biological processes.…”
Section: Discussionmentioning
confidence: 79%